Effect of Pioglitazone on the Fructose-Induced Abdominal Adipose Tissue Dysfunction - Alzamendi, Ana (2012)
Aim: To test the potential role of PPAR in the endocrine abdominal tissue dysfunction induced by feeding normal rats with a fructose rich diet (FRD) during three weeks. Methodology: Adult normal male rats received a standard commercial diet (CD) or FRD, (10% in drinking water) without or with pioglitazone (PIO) (i.p. 0.25 mg/Kg BW/day; CD-PIO and FRD-PIO). Thereafter, we measured circulating metabolic, endocrine and oxidative stress (OS) markers, abdominal adipose tissue (AAT) mass, leptin (LEP) and plasminogen activator inhibitor-1 (PAI-1) tissue content/expression, and leptin release by isolated adipocytes incubated with different concentrations of insulin. Results: Plasma glucose, insulin, triglyceride, TBARS, LEP and PAI-1 levels were higher in FRD rats; PIO co-administration fully prevented all these increments. AAT adipocytes from FRD rats were larger, secreted a higher amount of LEP and displayed decreased sensitivity to insulin stimulation; these effects were significantly ameliorated by PIO. Whereas AAT LEP and PAI-1 (mRNA) concentrations increased significantly in FRD rats, those of insulin receptor substrate (IRS)-1 and IRS-2 were reduced. PIO co-administration prevented FRD effects on LEP, PAI-1, and IRS-2 (fully), and IRS-1 (partially) mRNAs in AAT. Conclusion: PPARγ would play a relevant role in the development of the FRD-induced metabolic-endocrine dysfunction.